Pengaruh Optimalisasi Kebutuhan Gizi harian Anak Usia Dini Pada Perkembangan Anak Di Tk Miftahul Hidayah Tlagah - Ulfadilah (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2026)
Adequate daily nutritional intake in early childhood is a critical determinant of children’s cognitive, motor, and socio-emotional development. Suboptimal nutrition during this sensitive developmental period may lead to growth and developmental delays with long-term consequences. This study aims to examine the effect of optimizing daily nutritional intake on early childhood development at TK Miftahul Hidayah Tlagah. This study employs a cross-sectional design, with a recommendation for future longitudinal follow-up to assess long-term impacts. Measurements include assessment of daily dietary intake using the 24-hour dietary recall method and a simplified Food Frequency Questionnaire (FFQ), anthropometric status assessment based on weight-for-height indicators, and evaluation of child development using validated early childhood development instruments, such as the Ages and Stages Questionnaire (ASQ-3) or locally validated developmental scales. Data analysis is conducted using multiple linear regression and/or logistic regression models to examine the relationship between the adequacy of macro- and micronutrient intake and developmental scores. The expected findings indicate that children with adequate daily nutritional intake particularly sufficient protein, iron, and essential fatty acids tend to demonstrate higher cognitive and motor development scores compared to children with inadequate nutritional intake. These findings are consistent with national and international evidence highlighting the importance of nutrition in early childhood development. In conclusion, optimizing daily nutritional intake has significant potential to enhance early childhood development. Therefore, nutrition education interventions for parents and food service providers in kindergarten settings are strongly recommended as promotive and preventive strategies to support optimal child growth and development.